Consequence of intensity controlled aerobic dance on pulmonary function - Sabaananth, S.; Thevanthy, T. (All Saint's College, Trivandrum India, 2015)
Breathing is one of the critical bodily function which the lungs deliver vital oxygen to the blood, and expire carbon dioxide out of the body. Dance training can help to strengthen and make this system more efficient. The objective of this study was to find out the intensity controlled aerobic dance training on pulmonary function. To achieve the purpose thirty (N=30) women students were randomly selected from Jaffna, Sri Lanka as subjects and their mean age were 17 ± 1.3 years. They were practice aerobic dance 60±10min / day for 3 days / week over the period of twelve weeks. The intensity of the exercise was design according to the dancers maximum heart rate (Harvonen formula) and 5% intensity was progressively increased every two weeks from 60% - 85%. Data were collected on their Forced Vital Capacity (FVC), Forced Expiratory Volume (FEV1), Peak Expiratory Flow (PEF) by PC based USB Spirometer before and after the training period. The collected data were statistically treated by using paired sample ‘t’ test, 0.01 level of confidence was fixed to test the significance. The results shows that, Aerobic dance training significantly improve FVC, FEV1 and PEF. FVC shows better improvement (48.16 %), FEV1 (18.22 %) and PEF (24.17%). Hence it was concluded that, aerobic dance training optimistically influence on pulmonary function
Keywords: Aerobic dance; FVC; FEV1; PEF